Evaluasi Kesesuaian Lahan untuk Pengembangan Cabai Merah (Capsicum annuum L.) pada Lahan Pasca Vulkanik Gunung Sinabung di Kecamatan Naman Teran, Kabupaten Karo - Bilter Sirait; Ebsan M. Sianipar; Roni Martin (Majalah Ilmiah METHODA, 2026)
This study aimed to evaluate the level of land suitability for red chili pepper (Capsicum annuum L.) cultivation on land affected by the eruption of Mount Sinabung in Naman Teran District, Karo Regency. The study was conducted from December 2025 to February 2026 using a survey method with a spatial and descriptive analysis approach. The overlay of soil type, elevation, and slope gradient maps resulted in 13 Land Map Units (LMUs). However, eruption-affected areas were identified in two villages within specific LMUs. Land suitability evaluation was carried out using a matching method between land characteristics and crop suitability criteria. The results showed that the LMU in Sigarang-garang Village was classified as unsuitable (N), with nutrient retention and erosion hazard as the main limiting factors. Similarly, the LMU in Sukanalu Village was also classified as unsuitable (N), with comparable limitations. Some parameters, such as soil pH, can be improved through liming; however, nutrient retention remains a major constraint that is difficult to significantly improve.